Requirements validity of studies of environmental impact of mining activities in territories of indigenous people required by the case law INTER-AMERICAN court of human rights - Ruiz Molleda, Juan Carlos (2016)
The last proposal from the Ministry of Energy and Mines (MEM), about the exoneration from the Environmental Impact Study (EIS, onwards) the  realization  of  the  seismic  activity  in  the stage of exploration of oil lots, has allowed us a better visualization to of the EIS’s role in the defense of the territories of indigenous peoples. Similarly, it allows us to evaluate carefully how the way the MEM understands and realizes EISs meets the mandatory standards established by the jurisprudence of the Inter-American Court of Human Rights (IACH, onwards), the Convention No. 169 of the ILO and Peruvian Constitution. Then, given that the rules established in the jurisprudence of the IACH are mandatory, this article has three objectives: first, to generally review EISs treatment in the IACH’s jurisprudence; second, to identify the centrality of the livelihoods of indigenous peoples in the EISs about extractive activities; and, third, to establish the requirements set out by the IACH for the